FLEXIBLE EDUCATIONAL MODELS: A FRAMEWORK FOR INCLUSION IN THE RURAL CONTEXT - Bairon Edilberto Ramirez Rendon; Roanger Alexander Gamboa Bastidas (LÍNEA IMAGINARIA, 2025)
Educating in the 21st century requires educational systems to generate flexible academic proposals, capable of adapting to regional and local demands. These new proposals must also guarantee high levels of quality in education, competitiveness and equity. These challenges focus the attention of public policies and educational institutions to improve the relevance, coverage, effectiveness and efficiency of the system, assuming interculturality and addressing the different conditions of the rural context. Given this, the objective is to analyze from a theoretical component focused on the applicability of flexible educational models and the determining factors of adequate inclusion. Generating space to address elements that strengthen positions on the importance of flexibility in inclusive education, its adaptability and application in rural contexts. To this end, this article is oriented from a qualitative approach, from documentary design generating the possibility of presenting an essay-type text. Hence the importance of pedagogical flexibility, which must therefore provide for inclusive, pertinent, contextualized education in accordance with the interests and expectations of the various actors in the local and regional educational community, fostering strategies that dynamize classroom situations and encourage learning to know, to do, to be, to live together, to participate, to undertake and innovate and to understand the world in a meaningful way from all ages and educational cycles. Likewise, it must guarantee the transition between educational levels and training modalities throughout life, through the existence of educational scenarios and programs that offer means to meet the levels of competencies and qualifications that are highly motivating, welcoming, effective and relevant to the employment situation, the needs and personal expectations of students in the rural context.